2020
DOI: 10.5114/aic.2020.101761
|View full text |Cite
|
Sign up to set email alerts
|

TransRadial versus transUlnar artery approach for elective invasive percutaneous coronary interventions: a randomized trial on the feasibility and safety with ultrasonographic outcome – RAUL study

Abstract: Introduction Transradial access (TRA) for coronary angiography (CAG) and percutaneous coronary intervention (PCI) is superior to transfemoral access (TFA). Transulnar access (TUA) is an alternative to TRA. Aim To compare the efficacy and safety of TRA vs. TUA in patients scheduled for CAG or PCI. Material and methods This was a prospective, single-center, randomized study conducted between 2013 and 2016. Two hundred patients referred for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This may exemplify prior research that has found a steeper learning curve when using ulnar artery access due to the artery's depth, weak palpability, and anatomical location close to the ulnar nerve. 3,5 In institutions where ulnar artery access is rarely performed, complication rates may be higher due to lack of training and exposure to the technique.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may exemplify prior research that has found a steeper learning curve when using ulnar artery access due to the artery's depth, weak palpability, and anatomical location close to the ulnar nerve. 3,5 In institutions where ulnar artery access is rarely performed, complication rates may be higher due to lack of training and exposure to the technique.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Ulnar artery catheterization has also gained recent popularity due to the perceived benefit it is larger, has a straighter course, and is less prone to vasospasm. 3,5 However, this also presents with potential risks as post catheterization occlusion of the ulnar artery may be less well tolerated. The ulnar artery tends to contribute more to the superficial palmar arch, and studies have shown the superficial arch contributes more blood flow to the digital arteries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The trans-ulnar approach (TUA) for cardiac catheterization is an attractive option for experienced operators who are skilled in this technique, especially in cases of anatomic variations of the radial artery or weak radial pulses [1][2][3] and has been associated with fewer bleeding complications. 4 Compartment syndrome is a rare but hand-threatening complication of trans-radial approach (TRA).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] RA also has advantages over ulnar access (UA). 7 However, some researchers still consider the ulnar artery a possible alternative to the radial artery (RadA) because of the relationship between the diameter of the artery and the weakening of the hand compressive force according to dynamometry data. 8 For the last 10 years, due to improvements in endovascular instrumentation and an increase in the manual skills of surgeons, RA has been actively used to treat pathologies in the peripheral arteries 9 and pelvic organs 10 and in neurointervention.…”
Section: Introductionmentioning
confidence: 99%